2022
DOI: 10.1161/circinterventions.120.010390
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Events Occur Early in Patients Undergoing Percutaneous Coronary Intervention and Are Reduced With Cangrelor: Findings From CHAMPION PHOENIX

Abstract: Background: Thrombotic events are reduced with cangrelor, an intravenous P2Y 12 inhibitor. We sought to characterize the timing, number, and type of early events (within 2 hours of randomization) in CHAMPION PHOENIX (A Clinical Trial Comparing Cangrelor to Clopidogrel Standard of Care Therapy in Subjects Who Require Percutaneous Coronary Intervention). Methods: CHAMPION PHOENIX was a double-blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This early occurrence of ST is consistent with results from a larger study, CHAMPION PHOENIX, which included patients with stable coronary artery disease or ACS without OHCA. In that study, most ischemic events were observed within the initial two hours following PCI [35]. The use of cangrelor in this study significantly reduced the number of ischemic events without an increase in bleeding complications [35].…”
Section: Discussionmentioning
confidence: 51%
“…This early occurrence of ST is consistent with results from a larger study, CHAMPION PHOENIX, which included patients with stable coronary artery disease or ACS without OHCA. In that study, most ischemic events were observed within the initial two hours following PCI [35]. The use of cangrelor in this study significantly reduced the number of ischemic events without an increase in bleeding complications [35].…”
Section: Discussionmentioning
confidence: 51%
“…Conversely, between 2 and 48 h after PCI, ischemic events occurred at similar rates between the cangrelor and clopidogrel. 40 A higher incidence of severe flow-limiting dissections and coronary perforations was observed in patients undergoing complex PCI. This risk is inherently associated with the intrinsic features of complex lesions and is less modifiable.…”
Section: Discussionmentioning
confidence: 99%
“…We agree that the evidence supports the importance of early and potent platelet P2Y12 inhibition with cangrelor during percutaneous coronary intervention. 1…”
Section: In Responsementioning
confidence: 99%
“…
We agree that the evidence supports the importance of early and potent platelet P2Y 12 inhibition with cangrelor during percutaneous coronary intervention. 1 The authors cited a meta-analysis of the three trials in the cangrelor CHAMPION (Cangrelor Versus Standard Therapy to Achieve Optimal Management of Platelet Inhibition) program that only analyzed subgroups with type 2 diabetes. However, the pooled, patient-level meta-analysis of these three trials 2 is more informative because the investigators were able to harmonize outcome definitions.
…”
mentioning
confidence: 99%